Fintech development and regulatory frameworks in Indonesia - Sukarela Batunanggar (Asian Development Bank Institute (ADBI), 2019)
This paper showcases the growth as well as the challenging factors for fintech development in Indonesia. As the eighth-biggest economy in terms of gross domestic product, and with an internet participation ratio of more than 50% and more than 50 million micro, small, and medium-sized enterprises (MSMEs), the country shows huge potential for fintech. As of 2017, 1.62 million had been distributed through 11 local peer-to-peer (P2P) platforms. However, low financial inclusion and the big financing gap among MSMEs pose a huge challenge, which the government is trying to overcome. Ensuring financial literacy will be key. An example is Finansilaku, which is providing online literacy programs for the development of the next generation. Moreover, fintech companies such as Mekar are creating shared value as P2P lending platforms for women, with a similar philosophy as Grameen Bank. Finally, this paper also discusses customers' reluctance to use fintech products and examines how regulators have adopted strategies related to regulation strategy, frameworks, market supervision, and innovation.
Keywords: G21; G23; 330; fintech; financial technology; Indonesia